Analisis dan Pengembangan Sistem Pembelajaran Matematika Berbasis Permainan Pada Mode Operasi Dasar - Aditya Fitriadi; Hilmy Abidzar Tawakal (Jurnal Informatika Terpadu, 2021)
Learning media is needed in basic math operations at the elementary level because it can help children learn math operations. The learning media used must be by the child's daily life to understand it easily. The rapid development of technology has resulted in children getting closer to smartphones and often using them to play games. This study will discuss the design and development of learning media for basic mathematics operations using a model-driven game development approach that produces mobile games on Android devices. The development method uses five stages of the agile version of the model-driven game development: envisioning, iteration modeling, model storming, test-driven development, and review. Unity chooses as the game development software in this study. The results of this study are the design and building of a mobile game application for learning basic math operations that are easily understood by elementary school children and can use by elementary math teachers.